2014
DOI: 10.1161/atvbaha.114.303031
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Adiponectin-Associated Perivascular Function in Vascular Disease

Abstract: T hroughout the body, most arteries and veins with an internal diameter >100 μm are invested with a layer of perivascular adipose tissue (PVAT), which comprises adipocytes, inflammatory cells, and stem cells in phenotypic states that depend on the body mass of the individual and their premorbid state. Known locations of PVAT include the coronaries, aorta, and the microvascular beds of the mesentery, muscle, and kidney. [1][2][3][4][5] The fat cells were often regarded as mere repositories for excess energy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 41 publications
0
52
0
2
Order By: Relevance
“…16 In contrast, recent studies in mesenteric vessels of wild-type mice advance that the vasorelaxing and hyperpolarizing effects of adiponectin rely on the opening of maxi Ca 2+ -activated K + (BK Ca ) channels. 28,29 In addition, a factor that might be adiponectin is released after stimulation of rat and murine mesenteric arteries with β3 adrenoreceptor. This latter factor seems to exert its paracrine effect by activation of AMPK and opening of BK ca channels.…”
Section: Pvrf: Potential Candidatesmentioning
confidence: 99%
“…16 In contrast, recent studies in mesenteric vessels of wild-type mice advance that the vasorelaxing and hyperpolarizing effects of adiponectin rely on the opening of maxi Ca 2+ -activated K + (BK Ca ) channels. 28,29 In addition, a factor that might be adiponectin is released after stimulation of rat and murine mesenteric arteries with β3 adrenoreceptor. This latter factor seems to exert its paracrine effect by activation of AMPK and opening of BK ca channels.…”
Section: Pvrf: Potential Candidatesmentioning
confidence: 99%
“…Adipose tissue is an active endocrine organ that secretes a variety of molecules that affect both glucose metabolism and cardiovascular function [1]. Recently, epicardial adipose tissue (EAT) has emerged as a novel target for the stratification of cardiometabolic risk factors due to its unique location and multifaceted metabolic properties with systemic and local effects [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although numerous subsequent animal studies and in vitro experiments have reported that adiponectin has direct anti-inflammatory, anti-atherogenic, antihypertensive (vasodilatory) and antidiabetic (insulinsensitizing) properties [11][12][13][14], many human studies have failed to show any association between hypoadiponectinaemia and cardiovascular events [15][16][17], and the possibility that a low circulating amount of adiponectin is merely an innocent bystander rather than a genuine risk factor for obesity-related disorders certainly exists.…”
Section: Discussionmentioning
confidence: 99%
“…Another distinct feature is that adiponectin has been found to be inversely related to anthropometric measures, such as BMI and waist circumference [5,9,10], and to other metabolic factors found to be associated with higher risk of type 2 diabetes, CHD and hypertension, for example circulating insulin, glucose and triglyceride concentrations [4][5][6]9,10]. Furthermore, numerous animal studies have reported that adiponectin exerts direct anti-inflammatory, anti-atherogenic, antihypertensive (vasodilatory) and antidiabetic (insulinsensitizing) properties [11][12][13][14]. Nevertheless, even though adiponectin has been associated with well-known cardiovascular risk factors [4][5][6][8][9][10], a number of studies have failed to show any association between hypoadiponectinaemia and cardiovascular events in human beings, as summarized in three recent systematic reviews and meta-analyses [15][16][17].…”
mentioning
confidence: 99%